Olfactory Sensitivity to Amino Acids in the Blackspot Seabream (Pagellus Bogaraveo, Brünnich 1768): How Effective is the Electro-olfactogram in Seawater? - Barata, Eduardo N. (2010)
Intensive aquaculture is heavily dependent on high-quality fishmeal to meet their protein requirements. However, due to the increased demand, decreased availability, raising costs and the potential presence of organic and inorganic contaminants, it is of economical and environmental interest to replace fishmeal by a renewable protein sources. This is particularly challenging since replacing fishmeal may lack appropriate chemical stimulants for active consumption. Fish have a well-defined olfactory sensitivity to L-amino acids (Hara, 1994), and this phenomenon is generally held to be involved in the location and identification of food (Carr et al., 1996). Olfactory sensitivity in fish can be assessed by electro-olfactogram (EOG); a field potential recorded from just above the olfactory epithelium (Scott and Scott-Johnson, 2002). Due to the high electrical conductivity of seawater, EOG responses recorded in marine fish are, however, of lower amplitude than those recorded in freshwater fish (Silver et al., 1976). It is unclear, however, to what extent EOG recording in seawater may underestimate the olfactory sensitivity of a given species when compared to more invasive recording methods, such as multi-unit recording from the olfactory nerve. The blackspot seabream is a promising new species for the finfish aquaculture industry; however, little is known about its biology. The current study investigated its olfactory sensitivity to amino acids and compared the efficacy of two different experimental approaches: multi-unit recording from the olfactory nerve and the electro-olfactogram (EOG). Cited references: Carr W.E.S., J.C. Netherton, R.A. Gleeson and C.D. Derby. 1996. Stimulants of feeding behavior in fish: analyses of tissues of diverse marine organisms. Biological Bulletin 190: 149-160. Hara T.J. 1994. The diversity of chemical stimulation in fish olfaction and gustation. Reviews in Fish Biology and Fisheries 4: 1-35. Scott J.W. and P. E. Scott-Johnson. 2002. The electro-olfactogram: a review of its history and uses. Microscopy Research and Technique 58: 152-160. Silver W.L., J. Caprio, J.F. Blackwell and D. Tucker. 1976. The underwater electro-olfactogram: a tool for the study of the sense of smell of marine fishes. Experientia 32: 1216-1217.